A new companion to digital humanities - Schreibman, Susan; Siemens, Raymond George 1966-; Unsworth, John 1958- (Chichester ; Malden, MA John Wiley & Sons, Ltd., 2016)
"A New Companion to Digital Humanities offers the most comprehensive and up-to-date collection of research currently available in this dynamic and burgeoning field"--Provided by publisher.
[3] Dissemination -- Interface as mediating actor / Stan Ruecker -- Saving the bits : digital humanities forever? / William Kilbride -- Crowdsourcing in the digital humanities / Melissa Terras -- Peer review / Kathleen Fitzpatrick -- Hard constraints : designing software in the digital humanities / Stephen Ramsay -- [4] Past, present, future of DH -- Beyond the digital humanities centre : institutional and financial contexts of the digital humanities / Andrew Prescott -- Sorting the digital humanities out / Patrik Svensson -- The digital humanities in a global context / Daniel Paul O'Donnell, Alex Gill, Katherine Walter, Neil Fraistat -- Gendering digital history / Laura Mandell -- The promise of digital humanities and the contested nature of digital scholarship / William G. Thomas III -- Building theories or theories of building? : a tension at the heart of digital humanities / Claire Warwick.
Prof. Jocelyn C. Pinzon (Recommending faculty) - Bookfair2017
Includes bibliographical references and index.
Keywords: Digital humanities; Humanities -- Methodology; Humanities -- Research; Digital media; Digital communications; Information storage and retrieval systems -- Humanities